Cardiovascular and behavioural risk factors in families with elevated lipoprotein(a)[Lp(a)]. (11th May 2021) - Chakraborty, A; Pang, J; Chan, D; Watts, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction Elevated lipoprotein(a)[Lp(a)] is an inherited and independent risk factor for atherosclerotic cardiovascular diseases (ASCVD). However, it is an under detected condition with no specific therapy available at present for lowering Lp(a). Hence, identifying the distribution of modifiable cardiovascular and behavioural risk factors is important for implementing an effective intervention programme to mitigate the overall risk of ASCVD in high-risk individuals with elevated Lp(a). Purpose: The primary aim was to describe and compare the distribution of modifiable cardiovascular and behavioural risk factors in both index cases and their relatives with elevated Lp(a) identified through cascade testing at the Lipid Disorders Clinic, Royal Perth Hospital. Methods: We studied 51 index cases and 71 relatives cascade tested with elevated Lp(a) (≥0.5 g/L). Questionnaires were completed concerning aspects of cardiovascular health (cholesterol level, blood pressure and blood glucose level) and behavioural health metrics (diet, smoking, physical activity, body-mass-index [BMI]). Lp(a) was measured by an immunoassay having minimal dependence on apolipoprotein(a) isoform size. The health metrics were described as proportions and statistical analyses performed using Student's t-test or Chi-square where appropriate. Results: Compared with the index cases, a higher proportion of their affected relatives were female (62% vs 43%, p = 0.039), younger (43 years vs 53 years, p < 0.001) and had lower Lp(a) levels (1.03 g/L vs 1.12 g/L, p = 0.003). A lower proportion of the affected relatives were treated for dyslipidaemia (31% vs 96%, p < 0.001). The affected relatives also had a lower incidence of ASCVD events (3% vs 37%, p < 0.001), hypertension (21% vs 43%, p = 0.003), and lower HbA1c levels (5.3% vs 5.9%, p = 0.031) compared with index cases. Additionally, a larger proportion of the affected relatives had ideal cardiovascular health (35% vs 14%, p = 0.008) compared with their index cases. However, more than half of the index cases and their relatives did not maintain a healthy diet (59% and 69%, respectively) and an ideal BMI (68% and 59%, respectively). Conclusion(s) Although the younger affected relatives with elevated Lp(a) have a lower cardiovascular risk compared with the index cases, a focus on modifiable behavioural changes, such as a healthy diet and an ideal body weight, is still required to mitigate the overall risk of ASCVD.